Effect of Silver Nanoparticles on Biofilm Formation and EPS Production of Multidrug-Resistant Klebsiella pneumoniae. (20th April 2020) - Siddique, Muhammad Hussnain; Aslam, Bilal; Imran, Muhammad; Ashraf, Asma; Nadeem, Habibullah; Hayat, Sumreen; Khurshid, Mohsin; Afzal, Muhammad; Malik, Imran Riaz; Shahzad, Mudassar; Qureshi, Umber; Khan, Zia Ul Haq; et al.
Abstract : Antibiotic resistance against present antibiotics is rising at an alarming rate with need for discovery of advanced methods to treat infections caused by resistant pathogens. Silver nanoparticles are known to exhibit satisfactory antibacterial and antibiofilm activity against different pathogens. In the present study, the AgNPs were synthesized chemically and characterized by UV-Visible spectroscopy, scanning electron microscopy, and X-ray diffraction. Antibacterial activity against MDR K. pneumoniae strains was evaluated by agar diffusion and broth microdilution assay. Cellular protein leakage was determined by the Bradford assay. The effect of AgNPs on production on extracellular polymeric substances was evaluated. Biofilm formation was assessed by tube method qualitatively and quantitatively by the microtiter plate assay. The cytotoxic potential of AgNPs on HeLa cell lines was also determined. AgNPs exhibited an MIC of 62.5 and 125  μ g/ml, while their MBC is 250 and 500  μ g/ml. The production of extracellular polymeric substance decreased after AgNP treatment while cellular protein leakage increased due to higher rates of cellular membrane disruption by AgNPs. The percentage biofilm inhibition was evaluated to be 64% for K. pneumoniae strain MF953600 and 86% for MF953599 at AgNP concentration of 100  μ g/ml. AgNPs were evaluated to be minimally cytotoxic and safe at concentrations of 15-120  μ g/ml. The data evaluated by this study provided evidence of AgNPs being safe antibacterial and antibiofilm compounds against MDR K. pneumoniae .